Novel Use of Calcimimetic Activity to Diagnose Primary Hyperparathyroidism in a Patient With Persistently Low-Normal Parathyroid Hormone Level - Bandaru, Sindhura (Cureus, 2020)
Primary hyperparathyroidism (PHPT) is the most common etiology of hypercalcemia in the ambulatory setting and usually presents with an intact parathyroid hormone (PTH) level that is elevated or inappropriately near the upper limit of the laboratory reference range. However, PHPT with low-normal PTH level is reported in the peer-reviewed literature, and this atypical presentation may delay diagnosis of PHPT. We present a case of PHPT with persistently low-normal PTH level in which the PTH dependence of hypercalcemia was demonstrated by the response to treatment with the calcimimetic agent cinacalcet.